Bibliometric Analysis of Studies on Empathy and Empathic Thinking Skills - Bekiroğlu, Derya; Güllühan, Nur Ütkür (Mimbar Sekolah Dasar, 2024)
Empathy, a crucial social skill that can lead to positive results, has gained more attention in recent years. This study aims to systematically examine research on empathy and empathy skills. For this purpose, within the scope of the research, studies on empathy and empathic thinking skills were subjected to bibliometric analysis. Analyzing bibliographic information is one of the most important methods for tracking aspects of scholarly communication, assessing research trends, and determining the priorities of research fields. Since this study focuses on the trends of studies on empathy and empathic thinking skills, the method of the research was determined as bibliometric analysis. The study group of the research consists of between the years 2013-2023 1135 articles accessed from the Web of Science database. According to the first finding of the research, it was seen that studies on empathy were mostly published in 2014. Additionally, most of the studies were published in the journal "Social Cognitive".The third observation is that most research is conducted in the health field. Following it were psychology and education. A fourth conclusion was that the correlation design, one of the quantitative research methods, was preferred. Additionally, It was determined that the sample levels of the studies were primarily adults and university students, and the sample size was between 31-100. It was observed that descriptive analysis, correlation, and ANOVA were mainly used in data analysis of the studies. In light of the findings obtained from the research, it is suggested that empathy-based studies can be carried out with preschool, primary school, and young children, and the number of meta-analysis and meta-synthesis studies can be increased.